(untitled) (Eurasian Medical Research Periodical, 2025)
Pulmonary hypertension (PH) is a disease characterized by increased pressure in the pulmonary vessels. In most cases, PH develops as a secondary condition, but there are also idiopathic forms. If symptoms suggestive of PH or other organic pathologies appear, all patients are recommended to undergo echocardiography (EchoCG) of the heart. The probability of PH is estimated by the peak velocity of tricuspid regurgitation on EchoCG and characteristic signs of the disease. EchoCG allows for the prompt detection of PH and referral of the patient to a specialized or regional center for further examination and treatment.The main task of such centers is to determine the PH group (according to the classification), evaluate its hemodynamic parameters and decide on the need for specific therapy. Patients who contact these centers must undergo a complete examination. For accurate diagnosis of PH, invasive catheterization of the right heart is required, which is available only in specialized medical institutions. This procedure also allows for assessing the possibility of prescribing calcium channel blockers and increasing the effectiveness of the vasoreactive test. If the vasoreactivity test is negative, the patient is prescribed specific therapy. Treatment components are selected individually and can only be prescribed by experts in specialized centers. Given the high cost of LH therapy, the emergence of high-quality generics can significantly reduce treatment costs while maintaining comparable effectiveness. In a new drug from the class of endothelin receptor antagonists was registered in Russia - Bozenex (bosentan), which has proven its bioequivalence to the original drug.